Composite metal material applied to unmanned aerial vehicle and preparation method of composite metal material

By using an aluminum-based alloy core layer and surface aluminum alloy part in the drone structural materials, and adding an intermediate Zn layer to the rolling process, the problem of insufficient surface adhesion of the drone materials under small sizes and harsh environments is solved, and higher bendability and adhesion are achieved.

CN119840248AActive Publication Date: 2025-04-18동관 화옌 뉴 매터리얼 테크놀로지 씨오 엘티디
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510080988.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Existing UAV structural materials are difficult to achieve large angle bending or distortion under small and medium sizes, and the surface adhesion is insufficient in harsh environments.

Method used

Using a composite metal material of the aluminum-based alloy core layer and the surface aluminum alloy part, the intermediate Zn layer is added through a specific alloy composition and rolling process to improve the material's bendable toughness and surface adhesion.

Benefits of technology

The large-angle bending capability and surface adhesion of composite metal materials in miniaturized components is improved, meeting the working needs of drones in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119840248A_ABST
    Figure CN119840248A_ABST
Patent Text Reader

Abstract

The invention relates to a composite metal material applied to an unmanned aerial vehicle and a preparation method thereof.The composite metal material comprises a core layer part made of aluminum base alloy, surface layer aluminum alloy parts arranged on the upper surface and the lower surface of the core layer part and an optional middle Zn layer; external components and load-bearing distortion components of the unmanned aerial vehicle suitable for working in a severe environment for a long time are effectively improved, the large-angle bending requirement and the surface layer adhesive force requirement required by small-sized components are improved, and meanwhile the basic requirement and other mechanical properties of light-weight materials are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite metal material, and in particular to a composite metal material used in an unmanned aerial vehicle and a preparation method thereof. Background Art

[0002] With the development of automatic control, artificial intelligence, and electronic information industries, the field of unmanned aerial vehicles (also commonly known as "drones") has made great progress. Unmanned aerial vehicles used in various fields have been developed, and many products have been put on the market. In the field of drone fuselage materials, high-strength and lightweight metal materials and composite materials have been widely used in drone body structures due to their advantages such as high specific strength, high specific modulus, and light weight. However, with the deepening of drone applications, many unmanned aerial vehicles need to work for a long time under harsh working conditions, such as earthquake relief, forest fire fighting, etc., which require the size of drones to be relatively small, and at the same time, attach large loads when necessary. When the weight and size of unmanned aerial vehicles are reduced, their structural materials are required to be able to undergo large-angle bending or twisting (greater than 90 degrees, or even greater than 120 degrees) in small and medium sizes to form fuselage components, which puts higher requirements on the application of metal composite materials.

[0003] There have been many studies and products exploring the structural materials of drones. For example, patent publication CN118124213A discloses a wear-resistant and lightweight composite metal material for drone casings. The patent document provides a wear-resistant and lightweight composite metal material for drone casings, which can significantly improve the impact strength of drone casings, and the molding process is relatively simple. However, this type of material does not take into account the performance requirements for rigid materials to be folded at large angles at corners or bends under the requirements of the size of medium-sized and small drones, nor does it take into account the working requirements of the material surface under long-term harsh working conditions. Summary of the invention

[0004] The purpose of the present invention is to solve one or more deficiencies in the above-mentioned prior art, and to improve the bending toughness, surface coating firmness and other mechanical properties of composite metal materials used in drones by utilizing specific alloy composition, rolling process and the arrangement of each layer.

[0005] A first aspect of the present invention provides a composite metal material applicable to a drone, the composite metal material comprising a core layer portion composed of an aluminum-based alloy, and surface aluminum alloy portions disposed on upper and lower surfaces of the core layer portion, wherein the core layer portion composed of the aluminum-based alloy has the following composition expressed in weight %:

[0006] 0.8%≤Mg≤1.2%,

[0007] 0.5%≤Si≤0.8%,

[0008] Fe≤0.3%,

[0009] Cu≤0.1%,

[0010] Mn≤0.1%、

[0011] Cr≤0.1%、

[0012] 0.2%≤Zn≤0.4%,

[0013] Ti≤0.1%,

[0014] In addition to the above components, the rest are Al and inevitable impurities; and

[0015] The surface aluminum alloy portion has the following alloy composition shown in weight %:

[0016] Si≤0.20%、

[0017] Fe≤0.3%,

[0018] Cu≤0.1%,

[0019] Mn≤0.10%、

[0020] 0.8%≤Mg≤1.5%,

[0021] Cr≤0.1%、

[0022] 0.6%≤Zn≤1.2%; the rest is Al and unavoidable impurities

[0023] In a preferred technical solution, there is also an intermediate Zn layer between the core layer part composed of the aluminum-based alloy and the surface aluminum alloy part. The intermediate Zn layer exists between the core layer part composed of the aluminum-based alloy and the surface aluminum alloy part in a continuous or discontinuous state, and the maximum thickness of the intermediate Zn layer is less than 1 micron.

[0024] Furthermore, in a preferred technical solution, a portion of the Zn composition in the surface aluminum alloy portion comes from the intermediate Zn layer.

[0025] In a preferred technical solution, the thickness of the core layer composed of the aluminum-based alloy is about 4 mm to about 9 mm, the thickness of the surface aluminum alloy portion is about 0.5 mm to 1 mm, and the thickness of the composite metal material is about 5 mm to about 10 mm.

[0026] A second aspect of the present invention provides a method for manufacturing a composite metal material applicable to a drone, the method comprising the following steps:

[0027] Step 1) Casting aluminum alloy blank

[0028] A casting process is used to obtain an ingot of an aluminum-based alloy, and a cast aluminum alloy blank is obtained from the ingot;

[0029] Step 2) Homogenization of cast aluminum alloy billets

[0030] The cast aluminum alloy blank obtained in step 1) is subjected to a homogenization treatment in a melting furnace at a homogenization temperature of 500-650° C. for 1 to 3 hours to obtain a homogenized cast aluminum alloy blank;

[0031] Step 3) Forming the initial surface aluminum alloy part

[0032] The upper and lower surfaces of the homogenized cast aluminum alloy blank are treated by an immersion bath containing Zn ions to plate an intermediate Zn layer;

[0033] Applying a preliminary surface layer aluminum alloy portion on the surface of the cast aluminum alloy billet on which the intermediate Zn layer is deposited;

[0034] Step 4) Hot rolling process

[0035] The cast aluminum alloy blank obtained in step 3) is fed into a hot rolling device to perform one or more hot rolling processes, and in at least the first or first two hot rolling processes, the hot rolling temperature is maintained at greater than 550° C. After the hot rolling is completed, the hot rolled strip is cooled and curled to obtain a hot rolled composite metal strip;

[0036] Step 5) Cold rolling process

[0037] The hot-rolled composite metal strip obtained in step 4) is sent to a cold rolling device for cold rolling, and cold rolling is performed in one pass or multiple passes to obtain a cold-rolled composite metal strip;

[0038] Step 6) Solution annealing

[0039] The cold-rolled composite metal strip obtained in step 5) is sent to an annealing furnace for annealing, wherein the annealing temperature is greater than 600° C. and the annealing time is controlled to be less than 1 minute; and

[0040] The strip after the solution annealing is cooled and coiled again to obtain a composite metal material that can be applied to drones. The composite metal material that can be applied to drones includes a core layer part and a surface aluminum alloy part located on the surface of the core layer part.

[0041] In a further preferred technical solution, the method specifically comprises the following steps:

[0042] Step 1) Casting aluminum alloy blank

[0043] The ingot of the aluminum-based alloy is obtained by a casting process to obtain a cast aluminum alloy blank, wherein the cast aluminum alloy blank has the following components represented by weight % composition:

[0044] 0.8%≤Mg≤1.2%,

[0045] 0.5%≤Si≤0.8%,

[0046] Fe≤0.3%,

[0047] Cu≤0.1%,

[0048] Mn≤0.1%、

[0049] Cr≤0.1%、

[0050] 0.2%≤Zn≤0.4%,

[0051] Ti≤0.1%,

[0052] In addition to the above components, the rest is Al and inevitable impurities;

[0053] Step 2) Homogenization of cast aluminum alloy billets

[0054] The cast aluminum alloy blank obtained in step 1) is subjected to a homogenization treatment in a melting furnace at a homogenization temperature of 550 to 560° C. for 1 to 2 hours to obtain a homogenized cast aluminum alloy blank;

[0055] Step 3) Forming the initial surface aluminum alloy part

[0056] The cast aluminum alloy blank after homogenization is subjected to degreasing treatment, and the blank is placed in a sodium hydroxide solution with a concentration of 50-100 g / L at 50-60° C. to remove the Al oxide film on the surface; subsequently, the surface of the cast aluminum alloy blank after the surface treatment is washed with pure water, and placed in a zinc sulfate solution with a concentration of 50 to 150 g / L for zinc precipitation treatment for 1 to 10 minutes to replace an intermediate Zn layer deposited on the surface of the cast aluminum alloy blank, wherein the thickness of the intermediate Zn layer is 1 to 5 μm;

[0057] A preliminary surface aluminum alloy portion is applied on the surface of the cast aluminum alloy blank on which the intermediate Zn layer is deposited, the preliminary surface aluminum alloy portion having the following composition shown in weight %:

[0058] Si≤0.20%、

[0059] Fe≤0.3%,

[0060] Cu≤0.1%,

[0061] Mn≤0.10%、

[0062] 0.8%≤Mg≤1.5%,

[0063] Cr≤0.1%、

[0064] 0.5%≤Zn≤1.0%;

[0065] The rest is Al and unavoidable impurities.

[0066] The thickness of the applied preliminary surface layer of aluminum alloy is 1 mm to 2 mm;

[0067] Step 4) Hot rolling process

[0068] The cast aluminum alloy blank obtained in step 3) is fed into a hot rolling device to perform 4 to 6 hot rolling processes, wherein the hot rolling temperature is maintained at 580° C. to 600° C. in the first two hot rolling processes; and

[0069] The cast aluminum alloy billet is maintained at a temperature of 460°C or higher before entering the penultimate hot rolling pass;

[0070] Next, the hot-rolled blank that has formed a preliminary hot-rolled strip is cooled using a cooling device, gradually cooled to a temperature of 180 to 200° C., and then coiled to obtain a hot-rolled composite metal strip;

[0071] Step 5) Cold rolling process

[0072] The hot-rolled composite metal strip obtained in step 4) is sent to a cold rolling device for cold rolling, and cold rolling is performed in one pass or multiple passes to obtain a cold-rolled composite metal strip;

[0073] Step 6) Solution annealing

[0074] The cold-rolled composite metal strip obtained in step 5) is sent to an annealing furnace for annealing, the annealing temperature is controlled at 620 to 630° C., and the annealing time is controlled at 20 seconds to 40 seconds; then cooled to 200 to 250° C. and coiled; a composite metal material that can be used in drones is obtained; and

[0075] The composite metal material applicable to drones comprises a core layer portion and a final surface aluminum alloy portion located on the surface of the core layer portion, the thickness of the core layer portion is approximately 4-9 mm, and the thickness of the final surface aluminum alloy portion is approximately 0.5 to 1 mm.

[0076] In a further preferred technical solution, the final surface aluminum alloy part of the composite metal material applicable to the UAV has the following composition:

[0077] Si≤0.20%、

[0078] Fe≤0.3%,

[0079] Cu≤0.1%,

[0080] Mn≤0.10%、

[0081] 0.8%≤Mg≤1.5%,

[0082] Cr≤0.1%、

[0083] 0.6%≤Zn≤1.2%.

[0084] In other optional technical solutions, the composite metal material applicable to the UAV satisfies one of the following conditions:

[0085] The core layer portion directly contacts the final surface aluminum alloy portion located on the surface of the core layer portion without an intermediate Zn layer therebetween; or

[0086] The intermediate Zn layer exists between the core layer portion and the final surface aluminum alloy portion in a continuous or discontinuous state with a maximum thickness of the intermediate layer being less than or equal to 0.5 μm.

[0087] The method for manufacturing a composite metal material applicable to a drone described in the second aspect of the present invention can be used to manufacture the composite metal material applicable to a drone described in the first aspect. Conversely, the composite metal material applicable to a drone described in the first aspect of the present invention can be manufactured by the method described in the second aspect above.

[0088] The composite metal material applicable to unmanned aerial vehicles and the manufacturing method thereof provided by the present invention effectively improve the external components and load-bearing twisting components of unmanned aerial vehicles suitable for long-term operation in harsh environments, improve the large-angle bending requirements and surface adhesion requirements required for miniaturized components, and also meet the basic requirements for lightweight materials and other mechanical properties.

[0089] In the following, the technical solutions and advantages of the present invention will be explained and described in more detail in conjunction with specific implementation methods. It should be understood that the contents presented in the specification and specific implementation methods are only for the purpose of more clearly illustrating the technical solutions and advantages of the present invention, and do not limit the protection scope of the present invention. Those skilled in the art can obtain the changed technical solutions based on the disclosure of the specification for various reasonable transformations. As long as they do not deviate from the spirit of the present invention, the various changed technical solutions should be understood to be included in the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] The drawings in the display part of this application are intended to provide a further understanding of the technical solution of the present disclosure and constitute a part of the specification. They are used together with the specific implementation methods of the present application to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.

[0091] Figure 1 is a schematic flow chart of a hot rolling process of a composite metal material applicable to a UAV according to the present invention;

[0092] Figure 2 This is a SEM electron microscope image of a cross section of a strip of a composite metal material prepared according to Example 1 of the present invention after metallographic polishing and sample preparation;

[0093] Figure 3 1. It shows a bending angle test device for the sample of the present invention;

[0094] Figure 4 A schematic diagram showing the alloy composite bending angle α;

[0095] Figure 5 It is a schematic diagram of a load-bearing frame of an unmanned aerial vehicle fuselage made by using the composite metal material of the present invention.

[0096] The reference numerals in the various drawings may be simply represented as follows:

[0097] 100-slab cooling device; 200-hot-rolled billet; 300-slab cooling device; 400-hot-rolled strip; 401-core layer; 402-surface alloy covering part; 500-slab final cooling device; 600-hot-rolled coiler; 700-bending angle measurement; 800-side beam member of the load-bearing frame; 900-connecting member. DETAILED DESCRIPTION

[0098] The present invention is described in more detail hereinafter to facilitate understanding of the invention.

[0099] Before describing the specific implementation scheme, it should be noted that those skilled in the art can select appropriate raw materials according to the enlightenment and teaching of the present disclosure, and use relevant testing equipment to perform relevant tests and obtain corresponding results. For raw materials without specific manufacturers or pathways, those skilled in the art can select raw materials that meet corresponding requirements as reaction starting materials according to the disclosure and requirements of this specification. The reaction raw materials of the process part compounds are derived from the initial products synthesized in the preamble step of the present invention, which can also be understood according to the present disclosure.

[0100] First of all, it should be noted that the raw materials not described in the present invention are raw material varieties that can be obtained by those skilled in the art based on common technical knowledge and existing market products.

[0101] In addition, it should be noted that percentages indicated in the technical solutions, embodiments of the specification and the summary of the invention of the present invention are generally specifically described. If no special description is made on the concentration or percentage, it will refer to the mass percentage (wt%) or the unit related to mass, such as grams per liter (g / L). For example, the components used in the embodiments are generally referred to as mass percentages, while the solution can be expressed in g / L.

[0102] In addition, the present invention may adopt an open-ended component definition method such as "includes" or "comprising" to indicate that the embodiment of the present invention may include the main component / coating used, and may also include other subsidiary components / coatings. However, in a preferred embodiment of the present invention, it may only consist of the components and coatings defined in the present invention, without having to include any other components. For example, the composite metal material described in the embodiment of the present invention may include an aluminum alloy core layer, an aluminum alloy surface layer, and may also include other subsidiary layers (such as a Zn layer with a very small thickness), or other layers (such as a decorative layer) and / or other unavoidable layers (such as an oxide layer on the surface of the aluminum alloy after forming), etc. At the same time, in a preferred embodiment of the present invention, it may only consist of an aluminum alloy core layer, an aluminum alloy surface layer, and / or an intermediate Zn layer of the described components, and no longer have or include other intermediate layers or other coatings with significant main components. In the description of the technical solution, one layer is located above another layer, which usually means that one layer is directly located on another layer, and no other layers are separated in between. A layer is located between two layers, which may mean that the surface of the layer is directly in contact with the two layers.

[0103] Test experiment of the present invention

[0104] Before describing the preparation experiment example, the test process, standard, and characterization method used in the typical experiment of the present invention are briefly described. For methods and parameters not described, those skilled in the art can use known or recognized methods in the field of metal materials for measurement.

[0105] 1. Bending angle test (α)

[0106] It is necessary to briefly describe the process alloy flow of the bending angle test of the present invention, but those skilled in the art are not necessarily limited to this description and may perform the test using similar or other standard methods already available in the field of alloy material bending. Figure 3The test device for performing a bending test, with which the maximum bending angle can be determined, is schematically shown in the form of a partial macro camera photograph. The test device consists of a bending roller, which typically has a roller radius of 2.0 cm. The sample has previously been cut into a size of 800 mm×200 mm in a direction perpendicular to the rolling direction. The sample is then pre-stretched by 10% perpendicular to the rolling direction at a pre-stretching speed of 15 mm / min. The resulting sample is then cut into a size of 200×200 mm and conveyed to the bending device. Figure 3 The bending roller shown extends parallel to the rolling direction, so that the bending line also extends parallel to the rolling direction. At this time, the bending roller presses the sample between two rollers with a roller diameter of 2.0 cm with a force F. The two rollers are spaced 10 times the thickness of the sample. The roller force F is measured during the bending of the sample by the bending roller. If the roller force F reaches a maximum and then begins to gradually decrease, it means that the bending angle of the sample has reached a limit state, and the material may begin to fail (such as cracking of the layer, cracks or abnormal distortion). When the force F drops by 20N compared to the peak force, the test is stopped. The sample is then removed from the bending device and as shown in the figure. Figure 4 The measured bending angle 700 (α) is shown. The "bending angle" referred to in the embodiments and experiments of the present invention refers to the angle between the two sides of the bent metal composite material after reaching the maximum bending degree.

[0107] 2. Surface adhesion test

[0108] The present invention also involves testing the surface adhesion of the sample under harsh conditions, which has guiding significance for the use of UAV composite materials in complex external environments. Under typical test conditions, 3%wt acetic acid is selected for testing. The sample is first heated to about 45°C with 3%wt sodium bicarbonate Na 2 CO 3 The solution is rinsed quickly to clean the impurities and partial oxides attached to the surface, and the subsequent 3% acetic acid test may include an evaluation of the resistance of the surface aluminum alloy layer to a diluted acidic medium at about 100°C for 120 minutes. The test may include cutting a cross-hatched mark into a sample and placing the sample in a 3% acetic acid solution at about 100°C for 120 minutes, then removing and cooling the sample, and then performing an additional set of cross-cuts on each sample, with the tape placed over the cross-hatched area before and after the acid bath, and the tape is steadily removed at an angle of about 60° within 0.5 to 1 second. If the tape has no visible aluminum alloy coating peeling points, it is excellent (3 points), if the tape has visible surface layer scattered peeling points, it is qualified (2 points), if the tape has flaky peeling pieces, it is unqualified (1), and if the surface layer cracks, it is unqualified (0 points).

[0109] In addition, as the properties or parameters of composite metal materials are often tested, other related tests of the present invention can be performed with reference to existing industry standards or international / national standards. For example, the elongation of aluminum alloys (such as ultimate elongation, elongation at break) can be performed with reference to the relevant contents of the international standard ISO 6892-1:2016, and the tensile strength-related tests can be performed with reference to GB / T-228.1-2010, and no further description will be given in this specification.

[0110] Hereinafter, the composite metal material applicable to a drone and the preparation method thereof of the present invention will be specifically described in conjunction with the accompanying drawings of the specification.

[0111] Step 1) Casting aluminum alloy blank

[0112] The core layer of the aluminum alloy composite material is cast by a casting process. In the preparation method of the composite metal material of the present invention, a casting process in the related technology or the existing technology can be used, as long as the aluminum alloy meets the following composition expressed in weight %:

[0113] 0.8%≤Mg≤1.2%,

[0114] 0.5%≤Si≤0.8%,

[0115] Fe≤0.3%,

[0116] Cu≤0.1%,

[0117] Mn≤0.1%、

[0118] Cr≤0.1%、

[0119] 0.2%≤Zn≤0.4%,

[0120] Ti≤0.1%,

[0121] In addition to the above components, the rest are Al and inevitable impurities. In order to ensure the subsequent mechanical properties of the metal composite material, the total amount of impurities in the core layer is no more than 0.10%wt, and the mass of a single impurity is preferably no more than 0.03%.

[0122] According to a preferred embodiment of the present invention, the alloy components within the above range are preferred, which helps to realize the application of the present invention to unmanned aerial vehicle structural parts or external supports. Relevant experiments believe that when the Mg content is increased by more than 0.5%, it will affect the toughness and bending resistance of the aluminum alloy. However, according to the design of the present application, it is preferred that 0.8%≤Mg≤1.2%, while ensuring sufficient toughness and strength in the bending resistance test and coating. The inventor surprisingly found that when the Mg element is present in the aluminum alloy, adding a moderate high content of Zn (such as 0.2% to 0.4% wt) can make the magnesium-zinc grains form a better interlacing, ensuring the auxiliary strengthening effect of the Mg element on the strength of the aluminum alloy, while at the same time, the Si content can be moderately reduced, reducing the number of hard compounds in the MgSi that are not resistant to bending. However, a small amount of silicon helps to maintain the bonding between the various alloy elements and the solidification characteristics of the composite metal material. When the Si content is greater than 0.8%, the synthesis of too many MgSi intermediate hard particles with the high-strength auxiliary element Mg is not conducive to the properties of the metal composite material under the extreme bending state. In addition, the presence of a small amount of Fe contributes to the refinement of the grain boundaries between the metallographic phases, but the Fe content needs to be limited to a maximum of 0.3% by weight to avoid coarse precipitates. Copper can improve corrosion resistance, and the copper content can be limited to a maximum of 0.1% by weight. Manganese below 0.1% by weight can help inhibit the formation of coarse manganese precipitates. Although chromium (Cr) helps to form a fine structure, it should be limited to 0.1% by weight, thereby also avoiding coarse precipitates. In addition, it was unexpectedly found that in addition to assisting in improving the corrosion resistance of the alloy, the Zn element can also form a ZnMg crystal phase with a high content of Mg elements, which assists in obtaining improved bending resistance and coating adhesion. Titanium contributes to grain refinement during the casting process, but it should be limited to a maximum of 0.1% by weight to ensure good castability of the aluminum alloy. The composition of the core layer portion in a typical embodiment is shown in the following table.

[0123] Table 1: Composition of the core layer (weight percentage, wt%, the remainder is Al and impurities, omitted)

[0124]

[0125] Step 2) Homogenization of cast aluminum alloy blanks

[0126] The cast aluminum alloy billet in step 1) is subjected to a homogenization treatment in a melting furnace at a homogenization temperature of about 560° C. for 2 hours, thereby making the alloy components more evenly distributed in the billet to be rolled.

[0127] Step 3) Forming a preliminary surface aluminum alloy coating

[0128] In a typical process, a designated Zn layer is first deposited on a cast aluminum alloy billet, which will provide the composite metal with improved properties in subsequent testing.

[0129] In this embodiment, the cast aluminum alloy blank is degreased and alkali-etched at 50-60°C (placed in a sodium hydroxide solution with a concentration of 80-100 g / L) to remove the Al oxide film on the surface, so that the pure Al surface can be exposed; then, the surface of the die-cast aluminum alloy part after surface treatment is washed with pure water and placed in a zinc sulfate solution with a concentration of 100 g / L for zinc deposition for 2 to 5 minutes to replace a thin layer of zinc layer with certain adhesion. During deposition, the thickness of the Zn layer is ensured to be greater than 1 micron, and preferably, a Zn deposition layer of 3 to 5 microns is formed in this embodiment.

[0130] Subsequently, the aluminum alloy coating to be covered is prepared according to the following composition, wherein in an embodiment of the present invention, the preliminary surface aluminum alloy coating (before rolling and heat treatment) typically has the following alloy composition shown in weight %:

[0131] Si≤0.20%、

[0132] Fe≤0.3%,

[0133] Cu≤0.1%,

[0134] Mn≤0.10%、

[0135] 0.8%≤Mg≤1.5%,

[0136] Cr≤0.1%、

[0137] 0.5%≤Zn≤1.0%;

[0138] The rest is Al and unavoidable impurities, the maximum individual content of these impurities is 0.03%, and the maximum total content does not exceed 0.10%.

[0139] The above-mentioned aluminum alloy coating can be applied to both sides of the core layer by existing plating technology to form a wrapped state, for example, by melt plating (such as scraping after melt pouring), melt bath immersion, electroplating, etc., and the skilled person applies the aluminum alloy coating according to the alloy composition disclosed in the present invention. The coverage thickness of the surface aluminum alloy coating is maintained at 1mm to 1.5mm. In a typical implementation process, it is controlled to be about 1 to 1.2mm.

[0140] In the aluminum alloy coating, some elements are similar to those in the core layer, but the inventors found that further increasing the content of Mg and Zn is conducive to further improving the adhesion between the surface layer and the core layer and the bending resistance of the surface layer.

[0141] The percentage of the preliminary surface aluminum alloy coating in typical embodiments is shown in the following table.

[0142] Table 2: Preliminary composition of the surface layer (weight percentage, wt%, the remainder is Al and impurities, omitted)

[0143]

[0144] Step 4) Hot rolling process

[0145] The billet to be rolled with the surface aluminum alloy coating applied in step 3) is hot rolled using a hot rolling device (such as Figure 1 100 as shown in the figure) for hot rolling. In the hot rolling process in this embodiment, the hot rolling is controlled to a temperature greater than 550°C (580°C to 600°C in this embodiment). Hot rolling can be repeated for multiple passes (such as 4 to 6 hot rollings, and 5 hot rollings are selected in this embodiment). The figure only shows the state of one hot rolling process by way of example. The slab can be repeatedly moved left and right for multiple rolling passes. In the first or first two hot rollings, the temperature is maintained above 550°C, which is conducive to the fusion of the Zn layer and the overlying preliminary surface aluminum alloy coating.

[0146] The hot rolled blank 200 preferably has a temperature of at least 460° C. after leaving the hot rolling equipment 100 and before entering the penultimate hot rolling process, and preferably maintains a temperature of 480° C.-500° C. At this time, the hot rolled blank 200 that has been formed into a preliminary hot rolled strip 400 is cooled (such as air cooling or water cooling) in the above temperature range using the slab cooling device 300 and the auxiliary working rolls of the hot rolling equipment 100. The hot rolled strip 400 can be repeatedly moved left and right to perform two or more passes of hot rolling.

[0147] For example, in the embodiment, the hot-rolled strip is cooled to a temperature of 330-350° C. before the final hot rolling process, thereby further cooling the strip. To this end, the slab cooling device 100 sprays the hot-rolled strip with a cooled emulsion and accelerates the cooling of the hot-rolled strip. The working rolls of the hot rolling equipment also apply the emulsion and further cool the hot-rolled strip in the final hot rolling process to reduce the temperature. In this embodiment, the hot-rolled strip 400 has a temperature of 180 to 200° C. at the outlet of the slab final cooling device 500 after the final hot rolling process, and then is coiled at this temperature through the hot rolling coiler 600 to obtain a hot-rolled composite metal strip with a thickness of 10 mm to 15 mm.

[0148] In the process of the present invention, the above hot rolling temperature is conducive to controlling the appropriate grain hot rolled strip elongation at the end of the hot rolling process, otherwise it is not conducive to the preparation of large-angle bending toughness materials in the later stage. If the elongation is too large or too small, it is not conducive to effectively maintaining the corresponding crystal morphology between the various coatings of the steel billet during the cold rolling process.

[0149] Step 5) Cold rolling process

[0150] The hot rolled composite metal strip obtained in step 4) is sent to a cold rolling device for cold rolling. In this embodiment, the cold rolling can be performed by a cold rolling process known in the art, and one or more passes of cold rolling can be performed to obtain a 5 mm to 10 mm cold rolled composite metal strip.

[0151] 6) Solution annealing

[0152] The cold-rolled composite metal strip in step 5 is sent to an annealing furnace for annealing after being coiled. In this process, the annealing temperature is preferably greater than 600°C, typically controlled at 620-630°C, and lasts for 30 to 40 seconds, which will help the Zn coating layer that has initially penetrated into the aluminum alloy layer in the hot rolling process to more effectively penetrate and fuse with the core aluminum alloy and the surface aluminum alloy layer, and then quickly cooled to 200 to 250°C for coiling. A composite metal strip of 5 mm to 10 mm is obtained.

[0153] In the final composite metal strip, the thickness of the core aluminum alloy layer is about 4-9 mm, and the thickness of the surface layer (upper and lower layers) of the aluminum alloy covering layer is about 0.5 to 1 mm.

[0154] The inventor firstly made a longitudinal section of the final sample prepared in the typical embodiment 1 of the embodiment, and after the metallographic sample was pretreated, the SEM cross-section electron microscope observation was performed. Figure 2 shown. Figure 2 401 in the figure shows the core layer of the composite metal strip, and 402 is the surface alloy covering part. The different colored parts in the picture represent the different orientation positions of the grains or crystal phases. Between the core layer and the surface layer, no other layers can be seen.

[0155] In addition, from Figure 2 It can be seen from the cross-sectional electron microscope photograph that the boundary between the core layer part 401 and the surface alloy covering part 402 of the composite metal material strip is obvious, and the grain changes are large. The inventor is not limited to any theoretical explanation, but speculates that the possible situation is that the intermediate coating Zn layer plays a certain spacing role in a short time, and at the same time, the higher hot rolling temperature has a greater impact on the surface layer, promoting the faster growth and extension of the surface alloy grains with a high ZnMg composition.

[0156] In addition, the surface layer and the core layer in the embodiment were subjected to X-ray fluorescence spectroscopy to detect the various elemental components. The inventors found that the Zn content in the final surface aluminum alloy coating was slightly higher than that of the initial surface aluminum alloy coating, wherein the Zn content in the final surface layer was 0.1wt% to 0.2wt% greater than that in the initial surface layer, while the other components and the Zn component in the core layer were almost unchanged. In other words, the final surface aluminum alloy coating typically has the following alloy components shown in weight %:

[0157] Si≤0.20%、

[0158] Fe≤0.3%,

[0159] Cu≤0.1%,

[0160] Mn≤0.10%、

[0161] 0.8%≤Mg≤1.5%,

[0162] Cr≤0.1%、

[0163] 0.6%≤Zn≤1.2%; the rest is Al and unavoidable impurities, the maximum individual impurity of these impurities is 0.03%, and the maximum total amount does not exceed 0.10%.

[0164] In other words, in the final aluminum alloy composite material, part of the Zn content in the final surface aluminum alloy coating comes from the intermediate transition Zn layer between the aluminum alloy core layer and the aluminum alloy surface layer. The intermediate transition Zn layer in the process of the present invention may not exist at all in the final aluminum alloy composite material due to diffusion to the upper part, or may exist in a trace amount with a thickness of less than about 1.0 μm between the aluminum alloy core layer and the aluminum alloy surface layer.

[0165] The inventor believes that the Zn element in the embodiment of the present invention is more inclined to diffuse to the surface layer. On the one hand, the hot rolling temperature set in the process of the present invention is relatively high, and the effect of hot rolling on the surface layer is significantly higher than that on the core layer, so the high heat of the surface layer attracts the upward diffusion of the Zn element. In addition, the high Mg and low silicon content of the surface layer may control and reduce the amount of superhard MgSi compounds formed, which is also the reason for attracting Zn to fuse upward to a greater extent.

[0166] Comparative experiment

[0167] Hereinafter, the inventors conducted a series of comparative experiments to compare with the preferred embodiments of the invention.

[0168] Comparative Example 1

[0169] In Comparative Example 1, all the same alloy components as those described in Example 1 were implemented, and a process similar to that of Example 1 was adopted. The difference is that in the manufacturing process of Comparative Example 1, after the homogenization treatment of the cast aluminum alloy blank in step 2) of Example 1, the Zn deposition layer formation process was not performed in step 3), but the subsequent covering aluminum alloy coating process and the hot rolling step in step 4) were directly entered. Except for the above process, the same process as that of Example 1 was implemented, and its manufacturing process is not repeated here.

[0170] Comparative Example 2

[0171] In Comparative Example 2, all the same alloy components as those described in Example 1 were also implemented, and a process similar to that of Example 1 was adopted. The difference is that in the manufacturing process of Comparative Example 2, after the homogenization treatment of the cast aluminum alloy blank in step 2) of Example 1, the following process of step 3) was performed:

[0172] The cast aluminum alloy blank is degreased and alkali-etched at 50-60°C (placed in a sodium hydroxide solution with a concentration of 80-100g / L) to remove the Al oxide film on the surface, so that the pure Al surface can be exposed; then, the surface-treated die-cast aluminum alloy parts are placed in a zinc sulfate solution with a concentration of 150g / L for zinc deposition for 15 minutes to replace a thicker zinc layer. After deposition, the sample cross section is tested by SEM scanning microscope, showing that its thickness is about 20 microns to 30 microns.

[0173] Comparative Example 3

[0174] In Comparative Example 2, the same alloy components as those described in Example 1 were also implemented, and a similar process as that in Example 1 was adopted. The difference is that in the hot rolling process of step 4), the hot rolling temperature was controlled to be 480° C. to 500° C., and the rest of the process was the same as described in the example.

[0175] Comparative Examples 4-7

[0176] Comparative Examples 4-7 used the same process steps as described in the examples, but in the corresponding comparative examples, the core layer alloy components and the surface alloy components described in the following table were used.

[0177] Table 3: Composition of the core layer of the comparative experiment (weight percentage, wt%, the balance is Al and impurities)

[0178]

[0179] Table 4: Preliminary composition of the surface layer of the comparative experiment (weight percentage, wt%, the remainder is Al and impurities)

[0180]

[0181]

[0182] As can be seen from the above table, in the comparative experiment, Comparative Example 4 uses relatively lower Mg and Zn element contents than Example 1; in Comparative Example 5, a lower Si element content in the core layer is used than in Example 2, while the Si content in the outer layer is higher than that in the example; Comparative Example 6 uses a higher Fe content in the core and a higher Fe content in the outer aluminum alloy than in the example.

[0183] Next, the metal composite material samples of the embodiments and comparative examples were subjected to bending angle test (α), coating adhesion test (Ad) and other related extension and tensile strength tests. The test results are shown in Table 5 below.

[0184] Table 5: Mechanical properties of samples of the examples and comparative examples

[0185]

[0186]

[0187] From the test comparison of the embodiment scheme and the comparative experiment, it can be seen that the alloy product obtained by the composite metal material suitable for unmanned aerial vehicles in the embodiment of the present invention has achieved more excellent characteristics in the bending angle and surface adhesion test. The inventor will not be bound by any theoretical explanation for this, but believes that the above characteristics are related to the core layer, aluminum alloy components, the setting of the intermediate layer and the rolling process adopted by the present invention. Compared with the product without the Zn intermediate layer process, the product of the embodiment has correspondingly achieved a smaller bending angle and surface adhesion characteristics, which is related to the Zn intermediate layer partially or completely penetrating upward in the hot rolling process to form more ZnMg compounds. The inventor believes that the crystal phase of the ZnMg combination is conducive to increasing the grain extension and bending of the aluminum alloy composite product, and the transition fusion of Zn also consolidates the strength of the surface aluminum alloy coating. It is worth noting that when the Zn layer is too thick (such as comparative example 2), the surface Al alloy layer will have obvious slippage in the adhesion test, resulting in adhesion degradation, which is related to the soft properties of the Zn layer itself. Therefore, in the composite metal material product of the embodiment of the present invention, an independent continuous Zn layer may not exist between the final aluminum alloy core layer and the aluminum alloy outer coating layer. If an intermediate Zn layer exists, it may exist between the aluminum alloy core layer and the aluminum alloy surface layer in a continuous or discontinuous state in the form of a trace amount with a maximum thickness of the intermediate layer less than 0.5 μm. In addition, when the Mg and Zn in the aluminum alloy composite material components are excessively reduced (such as comparative example 4), the inventors found that the bending angle test was significantly insufficient compared with the embodiment, and when the Fe content or Si content was too high (comparative examples 5 and 6), the toughness and bending angle performance were insufficient, which may be related to the fact that Si and Fe will form a large hard compound intermediate phase in the aluminum alloy. In addition, higher primary and secondary hot rolling temperatures are significantly more conducive to the adhesion of the surface alloy layer of the strip and the surface bending resistance.

[0188] Application Examples

[0189] Figure 5The load-bearing frame of the fuselage of an unmanned aerial vehicle made of the composite metal material disclosed in the present invention is schematically described, including the side beam member 800 and the connecting member 900 of the load-bearing frame. The load-bearing frame shape and structure are typically suitable for connecting the middle beam of the middle part of the unmanned aerial vehicle. In small and medium-sized unmanned aerial vehicles, the vertical span and horizontal span of the frame are usually less than 50cm, or even less than 30cm. The member can be composed of a composite material based on the aluminum alloy of the present invention, and can be manufactured by appropriate forging, drawing, and bending processes. In the field of unmanned aerial vehicle applications, due to the limitation of the fuselage size itself, and often operating under harsh working conditions (such as the use of unmanned aerial vehicles in forest fire fighting or earthquake relief scenes), the fuselage components need to be bent at a large angle and bear a large load at the same time (such as the large-angle bending part in the load-bearing frame). At the same time, in a more optimal product, it is also required that the surface layer of the component does not fall off or crack under long-term harsh environment (such as acid and alkali corrosion, relatively high temperature) working conditions. The metal composite material of the embodiment of the present invention well realizes and improves these characteristics suitable for unmanned aerial vehicle components.

[0190] According to the implementation scheme and technical contents recorded in the specification of the present invention, the present invention can at least provide the following technical solutions: Although the present disclosure includes specific embodiments, it is obvious to those skilled in the art that various formal and detailed replacements or changes can be made to these embodiments without departing from the gist and scope of the invention of the present claims and their equivalent technical solutions. The embodiments described herein should be considered to be illustrative only and not for the purpose of limitation. The description of the features and aspects in each embodiment is considered to be applicable to similar features and aspects in other embodiments. Therefore, the scope of the present disclosure should not be limited by the specific description, but by the technical solutions of the claims, and all changes within the scope of the claims and their equivalents are interpreted as being included in the technical solutions of the present disclosure.

Claims

1. A composite metal material applicable to unmanned aerial vehicles, characterized in that: The composite metal material comprises a core layer portion composed of an aluminum-based alloy, and surface aluminum alloy portions arranged on upper and lower surfaces of the core layer portion, wherein the core layer portion composed of the aluminum-based alloy has the following composition expressed in weight %: 0.8%≤Mg≤1.2%, 0.5%≤Si≤0.8%, Fe≤0.3%, Cu≤0.1%, Mn≤0.1%、 Cr≤0.1%、 0.2%≤Zn≤0.4%, Ti≤0.1%, In addition to the above components, the rest are Al and inevitable impurities; and The surface aluminum alloy portion has the following alloy composition shown in weight %: Si≤0.20%、 Fe≤0.3%, Cu≤0.1%, Mn≤0.10%、 0.8%≤Mg≤1.5%, Cr≤0.1%、 0.6%≤Zn≤1.2%; the rest is Al and unavoidable impurities.

2. The composite metal material applicable to UAV according to claim 1, characterized in that: There is also an intermediate Zn layer between the core layer part composed of the aluminum-based alloy and the surface aluminum alloy part. The intermediate Zn layer exists between the core layer part composed of the aluminum-based alloy and the surface aluminum alloy part in a continuous or discontinuous state, and the maximum thickness of the intermediate Zn layer is less than 1 micron.

3. The composite metal material applicable to UAV according to claim 1 or 2, characterized in that: A part of the Zn composition in the surface aluminum alloy portion comes from the intermediate Zn layer.

4. The composite metal material applicable to drones according to any one of claims 1 to 3, wherein the thickness of the core layer portion composed of the aluminum-based alloy is about 4 mm to about 9 mm, the thickness of the surface aluminum alloy portion is about 0.5 mm to 1 mm, and the thickness of the composite metal material is about 5 mm to about 10 mm.

5. A method for manufacturing a composite metal material applicable to an unmanned aerial vehicle, characterized in that: The method comprises the following steps: Step 1) Casting aluminum alloy blank A casting process is used to obtain an ingot of an aluminum-based alloy, and a cast aluminum alloy blank is obtained from the ingot; Step 2) Homogenization of cast aluminum alloy billets The cast aluminum alloy blank obtained in step 1) is subjected to a homogenization treatment in a melting furnace at a homogenization temperature of 500-650° C. for 1 to 3 hours to obtain a homogenized cast aluminum alloy blank; Step 3) Forming the initial surface aluminum alloy part The upper and lower surfaces of the homogenized cast aluminum alloy blank are treated by an immersion bath containing Zn ions to plate an intermediate Zn layer; Applying a preliminary surface layer aluminum alloy portion on the surface of the cast aluminum alloy billet on which the intermediate Zn layer is deposited; Step 4) Hot rolling process The cast aluminum alloy blank obtained in step 3) is fed into a hot rolling device to perform one or more hot rolling processes, and in at least the first or first two hot rolling processes, the hot rolling temperature is maintained at greater than 550° C. After the hot rolling is completed, the hot rolled strip is cooled and curled to obtain a hot rolled composite metal strip; Step 5) Cold rolling process The hot-rolled composite metal strip obtained in step 4) is sent to a cold rolling device for cold rolling, and cold rolling is performed in one pass or multiple passes to obtain a cold-rolled composite metal strip; Step 6) Solution annealing The cold-rolled composite metal strip obtained in step 5) is sent to an annealing furnace for annealing, wherein the annealing temperature is greater than 600° C. and the annealing time is controlled to be less than 1 minute; and The strip after the solution annealing is cooled and coiled again to obtain a composite metal material that can be applied to drones. The composite metal material that can be applied to drones includes a core layer part and a surface aluminum alloy part located on the surface of the core layer part.

6. The method for manufacturing a composite metal material applicable to a drone according to claim 5, characterized in that: The method specifically comprises the following steps: Step 1) Casting aluminum alloy blank The ingot of the aluminum-based alloy is obtained by a casting process to obtain a cast aluminum alloy blank, wherein the cast aluminum alloy blank has the following components represented by weight % composition: 0.8%≤Mg≤1.2%, 0.5%≤Si≤0.8%, Fe≤0.3%, Cu≤0.1%, Mn≤0.1%、 Cr≤0.1%、 0.2%≤Zn≤0.4%, Ti≤0.1%, In addition to the above components, the rest is Al and inevitable impurities; Step 2) Homogenization of cast aluminum alloy billets The cast aluminum alloy blank obtained in step 1) is subjected to a homogenization treatment in a melting furnace at a homogenization temperature of 550 to 560° C. for 1 to 2 hours to obtain a homogenized cast aluminum alloy blank; Step 3) Forming the initial surface aluminum alloy part The cast aluminum alloy blank after homogenization is subjected to degreasing treatment, and the blank is placed in a sodium hydroxide solution with a concentration of 50-100 g / L at 50-60° C. to remove the Al oxide film on the surface; subsequently, the surface of the cast aluminum alloy blank after the surface treatment is washed with pure water, and placed in a zinc sulfate solution with a concentration of 50 to 150 g / L for zinc precipitation treatment for 1 to 10 minutes to replace an intermediate Zn layer deposited on the surface of the cast aluminum alloy blank, wherein the thickness of the intermediate Zn layer is 1 to 5 μm; A preliminary surface aluminum alloy portion is applied on the surface of the cast aluminum alloy blank on which the intermediate Zn layer is deposited, the preliminary surface aluminum alloy portion having the following composition shown in weight %: Si≤0.20%、 Fe≤0.3%, Cu≤0.1%, Mn≤0.10%、 0.8%≤Mg≤1.5%, Cr≤0.1%、 0.5%≤Zn≤1.0%; The rest is Al and unavoidable impurities. The thickness of the applied preliminary surface layer of aluminum alloy is 1 mm to 2 mm; Step 4) Hot rolling process The cast aluminum alloy blank obtained in step 3) is fed into a hot rolling device to perform 4 to 6 hot rolling processes, wherein the hot rolling temperature is maintained at 580° C. to 600° C. in the first two hot rolling processes; and The cast aluminum alloy billet is maintained at a temperature of 460°C or higher before entering the penultimate hot rolling pass; Next, the hot-rolled blank that has formed a preliminary hot-rolled strip is cooled using a cooling device, gradually cooled to a temperature of 180 to 200° C., and then coiled to obtain a hot-rolled composite metal strip; Step 5) Cold rolling process The hot-rolled composite metal strip obtained in step 4) is sent to a cold rolling device for cold rolling, and cold rolling is performed in one pass or multiple passes to obtain a cold-rolled composite metal strip; Step 6) Solution annealing The cold-rolled composite metal strip obtained in step 5) is sent to an annealing furnace for annealing, the annealing temperature is controlled at 620 to 630° C., and the annealing time is controlled at 20 seconds to 40 seconds; then cooled to 200 to 250° C. and coiled; a composite metal material that can be used in drones is obtained; and The composite metal material applicable to drones comprises a core layer portion and a final surface aluminum alloy portion located on the surface of the core layer portion, the thickness of the core layer portion is approximately 4-9 mm, and the thickness of the final surface aluminum alloy portion is approximately 0.5 to 1 mm.

7. The method for manufacturing a composite metal material applicable to a drone according to claim 5 or 6, characterized in that: The final surface aluminum alloy part of the composite metal material applicable to the UAV has the following composition: Si≤0.20%、 Fe≤0.3%, Cu≤0.1%, Mn≤0.10%、 0.8%≤Mg≤1.5%, Cr≤0.1%、 0.6%≤Zn≤1.2%.

8. The method for manufacturing a composite metal material applicable to a drone according to claim 5 or 6, characterized in that: The composite metal material applicable to the UAV satisfies one of the following conditions: The core layer portion directly contacts the final surface aluminum alloy portion located on the surface of the core layer portion without an intermediate Zn layer therebetween; or The intermediate Zn layer exists between the core layer portion and the final surface aluminum alloy portion in a continuous or discontinuous state with a maximum thickness of the intermediate layer being less than or equal to 0.5 μm.

9. The method for manufacturing a composite metal material applicable to a drone according to any one of claims 5 to 8, characterized in that: The method produces a composite metal material that can be applied to unmanned aerial vehicles as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Wear-resistant light unmanned aerial vehicle shell composite metal material

    CN118124213A

  • Aluminum composite material with ALMGSI core alloy layer

    CN103857521A

  • Aluminum alloy clad material for molding

    CN104080935A

  • Clad 2xxx-series aerospace product

    EP3783125A1